Liming and potassium fertilization for sweet potato - Nogueira, Francisco Dias; de Carvalho, Vania Dea; Guimarães, Paulo Tácito Gontijo; de Paula, Miralda Bueno (Pesquisa Agropecuaria Brasileira, 1992)
A field experiment was carried out on EPAMIG experimental station at Cambuquira, MG, Brazil, in a Red-Yellow Latosol to study the effects of two liming rates (with and without), three K rates (60-120-180 kg of K2O/ha), applied wholly at the sume time and split three times on the growth and yield of roots of Malaca cultivar sweet potato (Ipomoea batatas Lam.). The lime rate was calculated by exchangeable Al + Ca + Mg method. The treatments improved the chemical soil conditions and nutrient contents of the shoots. The split K fertilization increased the marketable roots production. The largest yield of roots (27,335.2 kg/ha) was obtained in the liming absence. The starch and carotene contents in roots were favorably influenced by K treatments. Generally the liming and the K rates, contributed to improve the chemical soil conditions but, the split K application was the most important to increase the starch, carotene contents and root production.